Deteksi Dini Ventilator Associated Pneumonia Pada Pasien Terpasang Ventilator di Instalasi Perawatan Intensif RSUD Provinsi NTB - Atmaja, Hadi Kusuma; Kisid, Kristiani Murti (Majalah Kedokteran Nusantara The Journal Of Medical School, 2017)
Introduction The use of mechanical ventilator to the patients in intensive care unit (ICU) increases the risk of Ventilator Associated Pneumonia (VAP). The aim of this study was to detect the signs of nosocomial pneumomia by using Clinical Pulmonary Infection Score (CPIS) in the ICU patients with ventilators.Method A retrospective-descriptive study was conducted in Nusa Tenggara Barat Provinceâs general hospital with 15 patients and the data was analysed by univariate analysis.Hasil The majority of respondents (87 % or 13 patients) with mechanical ventilator were between 18-60 years old, 8 respondents (53%) were male and the indication of intensive care was due to brain injuries (66%). Among all respondents, 14 patients (93,3%) had CPIS value less than 6 (no VAP) and 1 patient (6,6%) had CPIS value above/equal to 6 (with VAP).Conclusion Based on this study, it is recommended to measure CPIS value to predict the risk of VAP.Key words : Mechanical Ventilation,CPIS, VAP